Investigating the Interaction between Inquiry Learning Models and Cognitive Styles in Predicting Students’ Physics Learning Outcomes - Nur Aisyah; Khaeruddin; A Sri Astika Wahyuni; Aulia Cahyani (Postgraduate, University of Mataram, 2026)
This study is a quasi-experimental study with a 2x2 factorial design. The aim of this research is to determine the effect of applying inquiry learning model and cognitive styles on the physics learning outcomes and the interaction between learning models and cognitive styles on physics learning outcomes. The population in this study were all physics students of grade XI, while the sample was taken from grades XI 2 and XI 6, which were selected based on the Cluster Random Sampling Technique. The research data were obtained by giving the GEFT test to students before using the learning model in this study, and the physics learning outcomes test was conducted after the application of the inquiry learning model. The data analysis technique used was ANOVA. Based on the inferential analysis, the Fcount (5.12) > Ftable (4.04), can be concluded that there’s a significant difference between students taught with GI and OI learning models, the Fcount (12.63) > Ftable (4.04), can be concluded that there’s a significant difference between students who have FI and FD cognitive styles, and the interaction value Fcount (4.19) > Ftable (4.04), can be concluded that there’s an interaction between learning models and cognitive styles on physics learning outcomes.